2019
DOI: 10.3389/fsufs.2019.00020
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistant Salmonella enterica Typhimurium Colonizing Chickens: The Impact of Plasmids, Genotype, Bacterial Communities, and Antibiotic Administration on Resistance

Abstract: The rise in Salmonella resistance to cephalosporins and fluoroquinolones has become a significant threat to public health. At issue, is whether agricultural use of antimicrobials is selecting antibiotic resistance in Salmonella and the degree to which large antimicrobial resistance gene reservoirs, present in animal manures, contribute to this resistance. Two in vivo studies were performed to address these questions. In the first study, chickens were administered Salmonella and commensals, including an Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
1
18
1
Order By: Relevance
“…This can be explained by the fact that E. coli are commensal pathogens of the poultry gut and they are more susceptible to antibiotic selective pressure and therefore development of resistance. Meanwhile, for Salmonella spp., it has been suggested that Gram-positive bacteria tend to acquire resistance genes from the resident bacteria in their environment (usually gram positive bacteria) and acquisition is influenced by the abundance of the resistance reservoir [ 29 ]. As E. coli spp.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that E. coli are commensal pathogens of the poultry gut and they are more susceptible to antibiotic selective pressure and therefore development of resistance. Meanwhile, for Salmonella spp., it has been suggested that Gram-positive bacteria tend to acquire resistance genes from the resident bacteria in their environment (usually gram positive bacteria) and acquisition is influenced by the abundance of the resistance reservoir [ 29 ]. As E. coli spp.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella is the primary and leading cause of food borne diseases globally; accounting for 78 million affected and 59 thousand deaths annually (52, 53). This is an endemic food borne disease in South Asian countries like Bangladesh (54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its potential to cause enteric disease, the detection of Salmonella isolates in poultry is of great concern which are globally recognized as food borne zoonoses (52, 55, 56). The severity and length of such diseases could reduce by antimicrobial therapeutics in human (53) and poultry as well (57, 58). However, the rising of antimicrobial-resistant that is, antimicrobials commonly prescribed to treat Salmonella are losing its ability to stop growing or killing of Salmonella has become a significant public health issue now days (Islam and Shiraj-um-mahmuda, 2016; Ahmed et al, 2019 Wasyl et al, 2015; Iwamoto et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New antimicrobial agents need to be accessible, easy to synthesize or extract, and effective, but must also be sustainable by not contributing to the rise of antibiotic resistance in ST, or in other bacteria by way of horizontal gene transfer and the antimicrobial resistome [ 14 ]. Plants and their byproducts are important candidate sources in the discovery of novel antimicrobials, primarily because of their availability, diversity of compounds and their complex chemical makeup [ 15 , 16 ]. Extracts prepared from various plant sources have been found to contain a vast array of bioactive organic small molecules with antimicrobial properties, particularly polyphenols.…”
Section: Introductionmentioning
confidence: 99%